Highest bush dog Speothos venaticus record for Ecuador with a potential association to a palm tree Socratea rostrata - Álvarez Solas, Sara (2020)
The bush dog (Speothos venaticus) is one of the rarest canids in Central and South America. Very little is known about its distribution or its ecological behavior. However, there are ongoing scientific efforts to compile updated data on this species. By using line transect surveys, interviews with local people and camera traps, we studied mammals and their association with four palm-tree species (Oenocarpus bataua Socratea spp., Iriartea deltoidea, and Wettinia maynensis). Three transects, of approximately 3 kilometers each, were used to survey the piedmont of Colonso-Chalupas Biological Reserve (CCBR) in Eastern Ecuador; a recently established biological reserve (93,246 ha with an altitudinal gradient from 560 to 4432 m asl). We recorded two independent events of bush dog at 1200 m asl, using line transect surveys (one event from 91 line transect surveys) and camera trapping (two photographs from 1759 trap-nights) from September 2016 to March 2017. Both occurred at the same location, where the ground was completely covered by mature S. rostrata fruits. This is the first scientific report which confirms: the presence of bush dog in the reserve, the highest elevation of its range in Ecuador, and provides relevant data on a direct or indirect association between bush dog and a palm tree.